2012
DOI: 10.1002/j.1556-6676.2012.00047.x
|View full text |Cite
|
Sign up to set email alerts
|

Counseling in the Philippines: Past, Present, and Future

Abstract: The history of colonization and persistent attempts at self‐governance in the Philippines parallel the beginnings of counseling in the country, which were largely influenced by the United States. Because of the Guidance and Counseling Act of 2004 and the Psychology Act of 2009, counseling is on its way to professionalization and regulation. Counseling is growing in depth and credibility, as evidenced by applications in practice that are not only indigenous but powerfully relevant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 5 publications
(8 reference statements)
0
22
0
Order By: Relevance
“…This finding is consistent with a previous study that reported low levels of burnout in school counselors in the Philippines (Poyaoan, 2007). In addition, the positive attitude and self-esteem of psychotherapists from the Philippines may have been influenced by the recent professionalization or certification of counselors and psychologists in the Philippines, acknowledging the importance and credibility of mental health services (Tuason, Fernandez, Catipon, Trivino-Dey, & Arellano-Carandang, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with a previous study that reported low levels of burnout in school counselors in the Philippines (Poyaoan, 2007). In addition, the positive attitude and self-esteem of psychotherapists from the Philippines may have been influenced by the recent professionalization or certification of counselors and psychologists in the Philippines, acknowledging the importance and credibility of mental health services (Tuason, Fernandez, Catipon, Trivino-Dey, & Arellano-Carandang, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, communication between patient and health professional was done through a go-between (tagapamagitan) especially when the professional was ibang tao. Hence, it is not surprising that openness to counseling is mediated by family and friends (Tuason et al, 2012). In interacting with an ibang tao health professional, Filipinos are formal, polite, and cordial, and may express agreement to medical advice, but may not necessarily comply.…”
Section: Preference For Lay Network and Mental Health Professional Amentioning
confidence: 99%
“…Furthermore, findings underscore the importance of attending not just to the intrapersonal context of teachers or distress of students, but also to the wider social, material, and structural challenges of their care work. This echoes how individual counselling issues in the Philippine setting are typically reflections of wider societal problems that set the parameters for how change and wellbeing can be fostered (Tuason et al, 2012 ).…”
Section: Discussionmentioning
confidence: 94%